Integrating fuzzy theory and visualization for QoS-aware selection of SaaS in cloud e-Marketplaces. Issue 1 (1st January 2021) - Ezenwoke, Azubuike; Adigun, Matthew
Abstract: Most cloud service e-marketplaces incorporate basic features like search and billing but lack more sophisticated elements that optimise users' experience. The cognitive demands of searching for and evaluating multiple cloud SaaS along multiple QoS criteria can be overwhelming, giving rise to what Alvin Toffler called choice overload . There is a need to integrate mechanisms that handles the vagueness that characterises the human decision-making process when finding suitable services. The objective of this paper is to reduce cognitive overload during cloud service selection in e-marketplaces by employing low cognitive demanding tools that leverage the dynamics of human expressions. We proposed a QoS-aware SaaS ranking and selection framework that integrates fuzzy theory and information visualisation for optimal decision-making in cloud e-marketplaces. An illustrative case study of Customer-Relationship-Management-as-a-Service e-marketplace demonstrated the framework's plausibility. The demonstration shows that our framework is a viable approach to rank and select SaaS in cloud e-marketplaces in a way that satisfactorily serves both the users of the platform and can potentially drive the business objectives of the e-marketplace.